Analysis of Employee Performance Indicators Using the Human Resource Scorecard Approach and Analytical Hierarchy Process - Chalisa, Risky Nor; Prawitasari, Dian (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Measuring employee performance is important for companies to carry out their business processes to meet people's electricity needs. This research aims to determine the most important indicators that can improve employee performance using the Human Resource Scorecard (HRSC) method approach and weighting using the Analytical Hierarchy Process (AHP). To find out the most important indicators, they are determined by accumulating key informant assessments in this research which are then analyzed using AHP with the help of the superdecision application. The research results show that the main perspective that must be considered is the customer perspective which has the highest priority weight. Then for each perspective on the HRSC theoretical approach, the key performance indicator (KPI) that PT PLN Pusmanpro Semarang must prioritize based on the highest priority weight is the KPI Reward amount (0.024351) in the financial perspective, KPI speed of service (0.134916 ) from the customer perspective, KPI for the number of projects implemented (0.023622) from the internal business process perspective, and KPI for increasing employee understanding of their job descriptions (0.035857) from the learning & growth perspective. To be able to improve the performance of its employees, PT PLN Pusmanpro Semarang must consider each of the most important indicators from each HRSC perspective.